The Nexus of Environmental Performance and Economic Growth: A Panel Analysis from Organization of Islamic Cooperation Countries - Khafidh, Muhammad; Jajang, Jajang; Junejo, Safiullah (Universitas Islam Internasional Indonesia, 2025)
The climate is changing and the earth is getting hotter. Cutting down rainforests, burning fossil fuels, and farming livestock all contribute to greenhouse gas emissions. Human economy and the natural world are closely connected. This study evaluates the relationship between environmental performance and economic growth using panel data for Asian member states of the Organization of Islamic Cooperation (OIC) for the years 2020 to 2022. Data on Environmental Performance Index and Gross Domestic Product growth were collected from the Yale Center for Environmental Law & Policy and the World Bank. Panel data regression was used by selecting the best parameter estimates from three panel data regression models: Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). The study findings are anticipated to enhance nations' consciousness regarding environmental concerns and to enhance their focus on ecologically sustainable economic growth and development trajectories.